#### Answer

$\color{blue}{y-3=\frac{3}{4}(x)}$

#### Work Step by Step

RECALL:
(1) The point-slope form of a line's equation is $y-y_1=m(x-x_1)$ where $m$=slope and $(x_1, y_1)$ is a point on the line.
(2) The slope $m$ of a line that contains the points $(x_1, y_2)$ and $(x_2, y_2)$ is given by the formula $m=\dfrac{y_2-y_1}{x_2-x_1}$..
Solve for the slope using the formula in (2) above to obtain:
$m=\dfrac{3-0}{0-(-4)}
\\m=\dfrac{3}{0+4}
\\m=\dfrac{3}{4}$
With a slope of $\frac{3}{4}$, either of the two given points can be used to write the point-slope form of the line's equation.
Therefore, using the point $(0, 3)$ gives:
$y-3 = \frac{3}{4}(x-0)
\\\color{blue}{y-3=\frac{3}{4}(x)}$